2005
DOI: 10.1007/s00415-005-0930-9
|View full text |Cite
|
Sign up to set email alerts
|

Corticospinal involvement in patients with a portosystemic shunt due to liver cirrhosis

Abstract: Hepatic myelopathy (HM) is a rare complication of chronic liver diseases usually associated with a portosystemic shunt, causing a progressive spastic paraparesis, and is likely to be overlooked. Thirteen patients with liver cirrhosis associated with surgical or spontaneous portosystemic shunts were studied to determine the frequency and gravity of HM. Six patients exhibited clear-cut signs of spinal cord involvement and four of them exhibited varying degrees of disability. Neurological examination did not reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 21 publications
3
31
0
Order By: Relevance
“…R. Nardone et al for their comments. We are in agreement that the motor evoked potentials (MEP) elicited by transcranial magnetic stimulation may be helpful in the diagnosis of hepatic myelopathy especially in patients with chronic liver disease associated with a portosystemic shunt [1]. But we think that MEP is not specific for this pathology.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…R. Nardone et al for their comments. We are in agreement that the motor evoked potentials (MEP) elicited by transcranial magnetic stimulation may be helpful in the diagnosis of hepatic myelopathy especially in patients with chronic liver disease associated with a portosystemic shunt [1]. But we think that MEP is not specific for this pathology.…”
mentioning
confidence: 55%
“…On the other hand, MEP could be abnormal in cirrhotic patients before hepatic encephalopathy is clinically manifesting [4]. This complication is more frequent than hepatic myelopathy in patients with chronic liver disease [1].…”
mentioning
confidence: 99%
“…21 In contrast, Nardone et al 5 found an abnormal CMCT to the lower lumbar spinal segments and a normal CMCT to the upper cervical spinal segments, thus supporting localization of main dysfunction to the thoracic spinal cord. Moreover, another MEP study of HM patients indicated that the sites of higher vulnerability are located between the upper thoracic and the lumbar spinal cord.…”
Section: Discussionmentioning
confidence: 96%
“…In particular, nitrogenous products such as ammonia have been identified as a major contributor to the development of HM. 17 Interestingly, Nardone et al 5 found that clinical and MEP results of patients with a more advanced stage of disease (with markedly prolonged CMCT) were not substantially altered by liver transplantation, whereas patients with strong evidence of early-stage disease (minor CMCT abnormalities) exhibited clear neurophysiological and clinical improvement after liver transplantation. These MEP findings suggest that HM may be reversible if treated in the early stages of the disease, 18,19 whereas spinal cord dysfunction remains unchanged or is less likely to be reversed by liver transplantation in the later stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation